Transformation methods for analysis of data on faecal egg count in sheep - MANDAL, AJOY; YADAV, N K; SHARMA, D K; ROUT, P K; ROY, R (The Indian Journal of Animal Sciences, 2011)
The study revealed that loge(FEC+100) transformation is the most appropriate transformation method for studying the effect of different factors on feacal egg count in a flock of Muzaffarnagari sheep. The feacal egg counts was good indicator of naturally infected nematode infection. The genetic factor like sire of the animal had only significant effect on logelO (FEC+25) and loge (FEC+I00) transfonned data and non-genetic effects, viz. sex and physiological status of ewes had significant effects on all transformed FEe data. Â